Assessment of pulmonary arterial compliance evaluated using harmonic oscillator kinematics. (1st June 2017) - Hayabuchi, Yasunobu; Ono, Akemi; Homma, Yukako; Kagami, Shoji
Abstract : We hypothesized that KPA, a harmonic oscillator kinematics‐derived spring constant parameter of the pulmonary artery pressure (PAP) profile, reflects PA compliance in pediatric patients. In this prospective study of 33 children (age range = 0.5–20 years) with various cardiac diseases, we assessed the novel parameter designated as KPA calculated using the pressure phase plane and the equation KPA  = (dP/dt_max) 2 /([Pmax – Pmin])/2) 2, where dP/dt_max is the peak derivative of PAP, and Pmax – Pmin is the difference between the minimum and maximum PAP. PA compliance was also calculated using two conventional methods: systolic PA compliance (sPAC) was expressed as the stroke volume/Pmax – Pmin; and diastolic PA compliance (dPAC) was determined according to a two‐element Windkessel model of PA diastolic pressure decay. In addition, data were recorded during abdominal compression to determine the influence of preload on KPA . A significant correlation was observed between KPA and sPAC (r = 0.52, P  = 0.0018), but not dPAC. Significant correlations were also seen with the time constant (τ) of diastolic PAP (r = −0.51, P  = 0.0026) and the pulmonary vascular resistance index (r = −0.39, P  = 0.0242). No significant difference in KPA was seen between before and after abdominal compression. KPA had a higher intraclass correlation coefficient than other compliance and resistance parameters for both intra‐observer and inter‐observer variability (0.998 and 0.997, respectively). These results suggest that KPA can provide insight into the underlying mechanisms and facilitate the quantification of PA compliance.